In hindsight a compendium of business continuity case studies - Clark, Robert A. (IT Governance Pub., 2014)
"What causes disasters? In this book, the authors analyse the causes of some of the major disasters from the last thirty years and explain what could have been done better, before and after the event. Unlike many titles on business continuity and disaster recovery, this title does not build up from the theory of business continuity planning. Instead, it takes apart real events such as Hurricane Katrina, the terrorist attacks in London, Madrid and Glasgow, and the collapse of Barings Bank, revealing the themes that contributed to each. Using these incidents as case studies, the authors demonstrate the potentially devastating results for organisations that have not planned for the worst. Crucially, the book proposes measures that could have helped to minimise the risks and consequences. By showing the potential repercussions of a badly designed disaster management and business continuity plan, this book helps you avoid making similar mistakes, reduce risks and enable faster recovery when things do go wrong."--
Includes bibliographical references. - Online resource; title from title page (Safari, viewed August 9, 2014)
Keywords: Business planning; Crisis management; Risk management; Strategic planning; Gestion de crise; Gestion du risque; Planification stratégique; risk management; COMPUTERS; System Administration; Disaster & Recovery